Kajian Pemikiran Ibnu Hazm tentang Pemberian Nafkah Istri Kepada Suami dan Implementasinya di Tengah Masyarakat NU Desa Pegaden Tengah Kecamatan Wonopringgo - Abdul latif, Muhammad (Al-Hukkam: Journal of Islamic Family Law, 2021)
This paper aims to seek and explore the problems of giving a wife a living to her husband which is the fruit of the thoughts of Ibn Hazm in its implementation in the NU community in Pegaden Tengah Village, Wonopringgo District. The research method used in this paper uses sociological juridical, with a qualitative approach. The data technique uses observation, interviews, and literature study. The technique of checking data is using triangulation and analysis using an interactive model. The results showed that Ibn Hazm's opinion was taken from the zhahir verse of the Qur'an which was then strengthened by the explanation of the companions (Qoul Alshahabiy) which showed that sometimes the wife is also obliged to provide a living, namely when the husband is poor and unable. Whereas in practice in the community in Pegaden Tengah Village, it shows that they are more the same in their application with Ibn Hazm's opinion, which is when the husband is unable to work due to several factors the wife feels obliged to provide for her husband and family.